Economic analysis of proceáing tomato growing: the case study of Torbali, west Turkey - Engindeniz, S.
(Es, En)
ilus., 28 ref.
Keywords: AGRICULTURA; CONTRATOS; ANALISIS ECONOMICO; ANALISIS DE COSTOS; RENDIMIENTO; PRECIOS; TOMATE; VIABILIDAD ECONOMICA; ESPAÑA